Control interno y la gestión financiera en la Municipalidad Provincial de Ucayali Contamana 2023 - Chiarella Espejo, Whitney Jane (2024)
The purpose of this final work was to determine the relationship between internal control and financial management in the Provincial Municipality of Ucayali, Contamana 2023, in which an applied-type study, level-descriptive with a non-experimental design was conducted, opting for a population of 43 workers of the finance department to whom a questionnaire of questions was used for the collection of information. The findings indicate that internal control is regular (26%), as officials and public servants occasionally do not have the necessary skills to manage different areas and the assessment of risks in internal control is not carried out adequately. Regarding financial management, it is rated as fair (26%), since only sometimes are there trained personnel to carry out an effective analysis. Finally, it was concluded that there is a significant relationship between internal control and financial management, supported by a Spearman's Rho coefficient of 0.822 and a bilateral significance of 0.000, which is lower. 0.05.